IMPLEMENTASI REGIONAL COMPREHENSIVE ECONOMIC PARTNERSHIP (RCEP) AGREEMENT OLEH INDONESIA TERHADAP PENINGKATAN FOREIGN DIRECT INVESTMENT (FDI) DI INDONESIA - NIM. A1011151150, GABEAN DEBORA NABABAN (Fakultas Hukum Universitas Tanjungpura, 2024)
Abstract The House of Representatives of the Republic of Indonesia has passed the Draft Law on the Regional Comprehensive Economic Partnership Agreement into law on September 27, 2022. As a follow-up to the signing of the Regional Comprehensive Economic Partnership Agreement, the Government of the Republic of Indonesia stipulated Law of the Republic of Indonesia Number 24 of 2022 concerning the Ratification of the Regional Comprehensive Economic Partnership Agreement. As for the purpose of ratifying the Regional Comprehensive Economic Partnership (RCEP) Agreement to support national economic development, Indonesia can carry out trade cooperation through international trade agreements with trading partner countries and take advantage of membership in regional and multilateral cooperation forums.Another purpose of the ratification of Law Number 24 of 2022 is to attract foreign investors to invest or invest in Indonesia. This is known as Foreign Direct Investment (FDI).Keywords: RCEP, FDI, UU No.24 Tahun 2022Abstrak DPR RI telah mengesahkan Rancangan Undang-Undang (RUU) tentang Regional Comprehensive Economic Partnership Agreement menjadi undang-undang (UU) pada 27 September 2022. Sebagai tindak lanjut atas penandatanganan Regional Comprehensive Economic Partnership Agreement (Persetujuan Kemitraan Ekonomi Komprehensif Regional), Pemerintah Republik Indonesia menetapkan Undang-Undang Republik Indonesia Nomor 24 Tahun 2022 tentang Pengesahan Regional Comprehensive Economic Partnership Agreement (Persetujuan Kemitraan Ekonomi Komprehensif Regional). Adapun tujuan pengesahan Regional Comprehensive Economic Partnership (RCEP) Agreement ini untuk mendukung pembangunan ekonomi nasional, Indonesia dapat melakukan kerjasama perdagangan melalui perjanjian perdagangan internasional dengan negara mitra dagang serta memanfaatkan keanggotaan dalam forum kerjasama regional dan multilateral.Adapun tujuan lainnya dari pengesahan Undang-Undang Nomor 24 Tahun 2022 yaitu untuk menarik minat para investor asing menanamkan modal atau melakukan investasi di Indonesia. Hal ini dikenal dengan istilah Foreign Direct Investment (FDI).Kata Kunci: RCEP, FDI, UU No.24 Tahun 2022.